2019
DOI: 10.2196/14819
|View full text |Cite
|
Sign up to set email alerts
|

Postinjury Complications: Retrospective Study of Causative Factors

Abstract: Background Injury care involves the complex interaction of patient, physician, and environment that impacts patient complications, level of harm, and failure to rescue (FTR). FTR represents the likelihood of a hospital to be unable to rescue patients from death after in-hospital complications. Objective This study aimed to hypothesize that error type and number of errors contribute to increased level of harm and FTR. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
2
6
1
Order By: Relevance
“…Previous studies in trauma patients that investigated comorbidities as a risk factor for complications frequently used either ASA classification or the Charlson Comorbidity Index (CCI) to score the severity of comorbidities [ 11 , 12 , 14 , 15 ]. A study by Lima et al of elderly hip fracture patients found that the CCI score was not independently associated with in-hospital delirium ( p ≥ 0.862), but heart disease and chronic obstructive pulmonary disease were [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in trauma patients that investigated comorbidities as a risk factor for complications frequently used either ASA classification or the Charlson Comorbidity Index (CCI) to score the severity of comorbidities [ 11 , 12 , 14 , 15 ]. A study by Lima et al of elderly hip fracture patients found that the CCI score was not independently associated with in-hospital delirium ( p ≥ 0.862), but heart disease and chronic obstructive pulmonary disease were [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regression analyses were performed crude and adjusted for covariates. Age, sex, ASA classification, and ISS were chosen as covariates for each separate radiologic abnormality parameter based on clinical experience and previous literature [ 10 15 ]. Furthermore, age is a risk factor for the radiologic parameters [ 16 18 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding patient factors that can affect FTR, age has been shown in several studies and in several healthcare settings to be associated with FTR, particularly in trauma populations [1,8,14,31,32,50,51]. Besides being associated independently with FTR, increasing age also relates with the risk of developing a cluster of complications, which also increases the risk of FTR [31].…”
Section: Factors That Affect Ftrmentioning
confidence: 99%
“…The comorbidities are also an important factor, since they contribute to the occurrence of complications41; 51, but also to FTR [3,14,31,32,41,50,51]. In trauma patients, the comorbidities associated with FTR are not consensual between studies, in a study the comorbidities associated with FTR were cardiac disease and bleeding disorders, whereas in another study, several comorbidities were associated with the development of complications, but only renal disease, liver disease and coagulopathy were associated with FTR, and reported that in other studies diabetes was also a risk factor for FTR [31,32].…”
Section: Factors That Affect Ftrmentioning
confidence: 99%